Pediatric Sciatic Neuropathies - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Prospective review of the incidence, cause, and prognosis of pediatric sciatic neuropathy (SN) in a 30-year experience of 53 patients is reported from the Department of Neurology, Children's Hospital Boston, Lahey Clinic, Burlington, MA, and Royal Children's Hospital, Melbourne, Australia.